A atuação do diretor de escola pública: determinações administrativas e pedagógicas do cotidiano escolar - Francisco, Iraci José (2006)
This work had as object of study the action of the director of the public school of São Paulo s State and their specific objectives were to understand and to explain his action in front of umpteen necessities that are announced such as to examine administrative requirements that arrive to the director resolves day by day, hampering his view to other fields of the school. The theoretical reference that gave support to the research consisted in studies and researches about school direction, detaching itself the following authors: José Augusto Dias, Vitor Henrique Paro e José Carlos Libâneo. The applied methodology began itself with study of exploratory character, with basis in question and observation in three schools; followed of available official documents, observation longer of a school and interview with its manager. The text includes the description and analysis of the action of the researched school. The choice of the schools initially studied, based itself in the index of school incomings raised by the South 1 Teaching Directorate and by the Evaluate System of School Incomings of São Paulo s State SARESP. The initial conjecture was that the director s action is come back mainly to the execution of the administrative labors and, in a second plan, to the pedagogic action in the school the results of the research confirmed partially such hypothesis, attesting the complexity of the director s action, because while middle-activity, the school administration introduces narrow relations with its end-activity, or better, the pedagogic process. We understand, therefore, that there are many determinants that explain the action of this professional, overloaded of expectation, that affronts the scholar quotidian in the complexity of the conditions of the functioning of public school